New best proximity points theorem for F-Suzuki proximal contractions: Chaowarit Phanthong, Winate Sanhan, Cherasak Mongkolkaeha - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we establish a new best proximity point theorem for F-Suzuki proximal contractions in complete metric spaces and show that our result contain some recent results. Also we give some illustrative examples of our main results.